Esophagobronchial fistula successfully managed with a self‐expandable metallic stent followed by fixation using a silicon Y stent. Issue 20 (31st August 2022) - Ohtsuka, Takashi; Kato, Daiki; Tsukamoto, Yo; Shibazaki, Takamasa; Nakada, Takeo; Yabe, Mitsuo; Hirano, Jun
Abstract: Esophagobronchial fistula (EBF) formation is a severe complication of advanced thoracic malignancies, that affects the prognosis and quality of life of patients. This study reports the case of an 80‐year‐old man with advanced esophageal cancer, complicated by EBF formation in the left main bronchus proximal to the carina following chemoradiation therapy. A fully covered stent was placed in the left main bronchus but was dislocated on the oral side. The attempt to place a partially covered self‐expandable metallic stent (SEMS) also failed due to stent dislocation on the oral side. To avoid stent dislocation, a partially covered SEMS with a length of 40 mm and a diameter of 16 mm was placed to cover the EBF in the left main bronchus. Then, a silicone Y stent (16 × 13 × 13 mm in outer diameter) was inserted to support the SEMS from the inside. After placing the SEMS and Y stent, the position of the SEMS was stabilized. The patient remained stable with adequate oral intake. Abstract : Esophagobronchial fistula (EBF) formation is a severe complication of advanced thoracic malignancies, that affects the prognosis and quality of life of patients. To avoid stent dislocation, a partially covered self‐expandable metallic stent (SEMS) with a length of 40 mm and a diameter of 16 mm was placed to cover the EBF in the left main bronchus. Then, a silicone Y stent (16 × 13 × 13 mm in outer diameter) was inserted to support the SEMS from the inside. After placing the SEMS and Y stent, the position of the SEMS was stabilized.